Analysis of Illocusary Speech Acts in Conversation on Social Media - Fauziyah Amalia (BIRCU, 2023)
Analyzing speech acts is an interesting thing for utterances in Indonesian. The background of this writing is because many people use WhatsApp social media to communicate nowadays. The purpose of this writing is to describe illocutionary speech acts and analyze illocutionary utterances in Fauziyah Amalia's personal whatsapp conversations. The source of data needed in writing is the source in the form of screenshots of conversations via WhatsApp which will later be converted into written text. This writing follows a pragmatic approach, the objects of this writing are some of Fauziyah Amalia's WhatsApp and WhatsApp contacts. In this pragmatic study, all the data needed and needed must be in the form of text. Based on the results of the discussion of writing, It can be concluded that illocutionary speech acts in whatsapp conversations 14 screenshots found 43 speech acts which were divided into 1) there were 21 assertive speech acts, 2) there were 11 directive speech acts, 3) there were 2 commissive speech acts, 4) there were expressive speech acts 6, and 5) there are 3 declarative speech acts. In private and group WhatsApp conversations Fauziyah Amalia uses more assertive, directive and expressive speech acts. The meaning of illocutionary acts, which means telling, complaining, begging, boasting, asking, proposing, ordering, warning, inviting, offering, declaring, praying, claiming, and making decisions.